Impact assessment of the Facilitadores Judiciales programme in Nicaragua - Maurits Barendrecht; Margot Kokke; Martin Gramatikov; Robert Porter; Morly Frishman; Andrea Morales (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Facilitadores Judiciales is a programme run by the Organization of the American States and the Nicaraguan judiciary. The main objective of the programme is to improve access to justice for the disadvantaged people in Nicaragua. From 1998 to 2010 the programme was implemented in almost all rural and isolated areas of the country. In 2010, facilitators were recruited and trained in many but not all urban municipalities. This presented an opportunity for a natural experiment to assess the impact of the programme and identify the 'drivers' for success. Before (2010) and after (2013) quantitative and qualitative studies were conducted in intervention and control areas. The quantitative results show confirmation of some of the hypothesised effects of the Facilitadores Judiciales programme. Other effects are indicated by the numerous in-depth interviews but are not substantiated by hard data. Most importantly, in the communities where facilitators were introduced the people report less legal problems. The facilitators are decreasing the costs of justice thus making it more accessible. Achieving more amicable solutions and thus promotion of social cohesion is another example of an impact of the programme. Several factors for success are identified. First, the gradual scaling-up of the programme from rural to urban areas promotes sustainability and facilitates knowledge management. Second, the paper identifies the specific challenges of piloting a trust-based access to justice programme in urban areas. Another set of challenges is the different impact that different facilitators make in their communities. Personal motivation, skills, and abilities, gained social authority, received training, and level of involvement of the local judges are seen as crucial for the facilitators' effectiveness. Active ownership on behalf of the Nicaraguan judiciary is another factor of success identified by the study. At the end, the paper discusses the possibilities for expanding the programme beyond Nicaragua.
Keywords: K00; K10; C93; 330; Access to justice; justice needs; paralegals; impact evaluation